Questioning Direct Cash Funds Regulation on Village Funds in Province of Bali during Covid-19 Pandemic - Astariyani, Ni Luh Gede; Hermanto, Bagus; Griadhi, Ni Made Ari Yuliartini; Dewi, Tjokorda Istri Diah Widyantari Pradnya (Kertha Patrika, 2022)
The objections of this article are to describe, analyze, combine, and maintain concurrent relationships between regulations, implementation of Direct Cash Fund regulations at the regional level, and determined or measured factors on Direct Cash Fund by regional governments. This study combined normative and empirical legal research, analyzed legal instruments, and conducted interviews with various apparatus and parties involved in the Direct Cash Fund. This research results demonstrate that Direct Cash Fund was an effective government instrument, both in terms of its regulation and implementation by central and regional governments, in assisting village governments in mitigating the COVID-19 pandemic effect, particularly on the poorest people, and sustaining village development agendas through the new Village Fund scheme within Direct Cash Fund allocation.